Exchange rate bands of inaction and hysteresis in EU exports to the global economy: The role of uncertainty - Ansgar Belke; Dominik Kronen (Research On Money in the Economy (ROME), 2017)
This paper estimates the role of policy and exchange rate uncertainty shocks for EU countries' exports to the world economy. We examine the performance of the four biggest economies, namely Germany, France, Italy and the UK, under policy and exchange rate uncertainty in ex-ports to some of the most important global export destinations (United States, Japan, Brazil, Russia, and China). For this purpose, we apply a non-linear model, where suddenly strong spurts of exports occur when changes of the exchange rate go beyond a zone of inaction, which we call "play" area - analogous to mechanical play. We implement an algorithm describing path-dependent play-hysteresis into a regression framework. The hysteretic impact of real exchange rates on exports is estimated based on the period from 1995M1 to 2015M12. Looking at some of the main export destinations of our selected EU member countries, the United States, Japan and some of the BRICs (Brazil, Russia and China), we identify significant hysteretic effects for a large part of the EU member countries' exports. We find that their export activity is characterized by "bands of inaction" with respect to changes in the real exchange. To check for robustness we estimate export equations for limited samples (a) excluding the recent financial crisis and (b) excluding the period up to the burst of the dotcom bubble and September 11th. In addition, we employ an economic policy uncertainty variable and an ex-change rate uncertainty variable as determinants of the width of the area of weak reaction of exports. Overall, we find that those specifications which take uncertainty into account display the best goodness of fit, with economic policy uncertainty dominating exchange rate uncer-tainty. In other words: the option value of waiting dominates the real exchange rate effect on the EU member countries' exports.
Keywords: F14; C51; 330; export demand; global economy; hysteresis; policy uncertainty; BRICs; play-hysteresis; real exchange rate; switching/spline regression